The New Industrial Relations in the US: Phase II - Barbash, Jack (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
The author examines phase II of the new industrial relations in the United States, the labor strategy of American management on the offensive.